Prarancangan Pabrik Monochlorobenzene Dari Benzene Dan Chlorine Kapasitas 175.000 Ton/Tahun - Mustofa, Ali, M. Mujiburohman, S.T., M.T., Ph.D, Eni Budiyati, S.T., M.Eng (2017)
Preliminary design of monochlorobenzene with a capacity of 175,000 tonnes per year is planned to operate for 330 days per year. This plant will be established in Cilegon with a land area of 23,000 m2 and the number of employees of 188 people. Monochlorobenzene is produced from benzene and chlorine in a fixed bed multitube reactor with ferric chloride (FeCl3) as catalyst. The reaction occures in the gas-liquid phase where the chlorine is gas and benzene is liquid, irreversible, exothermic, and operated in non-adiabatic and non-isothermal conditions at a temperature range of 55-66.47°C, and pressure of 2.36 atm. The need of raw materials of benzene and chlorine are 23,065.2427 kg per hour and 20,924.3393 kg per hour, respectively. The utility unit includes the supply of water as much as 222,475.7106 kg per hour, the supply of saturated steam of 4,117.0966 kg per hour obtained from the boiler with fuel oil as much as 365.79 liters per hour, the compressed air of 50 m3 per hour, and the main power source to meet the needs of electricity obtained from PLN and generator sets as backup with a capacity of 2,600kW. The monochlorobenzene plant requires a fixed capital of IDR1,682,070,766,145 and working capital of IDR834,499,796,826. The economic analysis of this plant results in a profit before tax of IDR849,151,337,971 per year, after tax profits of IDR636,863,503,479 per year. The Percent Return On Investment (ROI) before tax is 50.09% and after tax is 37.56%. The Pay Out Time (POT) before tax is 1.66 years and after tax is 2.10 years. The Break Even Point (BEP) is 45.07%, and the Shut Down Point (SDP) is 28.62%. The Internal Rate of Return (IRR) is 35.77%. From the economical analysis, it can be conclude that the monochlorobenzene plant is feasible to set up.